A rare case of stiff left atrial syndrome caused by both coconut left atrium and vertebral compression: a case report. Issue 3 (14th September 2019) - Ooka, Junichi; Matsumoto, Kensuke; Kondo, Morihiko; Otomo, Toshiyuki
Abstract: Background : Calcification of the left atrium (LA) is a rare condition and can be the result of long-standing rheumatic mitral stenosis or an unusual complication after mitral valve replacement. Cases of massive LA calcification have sometimes been referred to as those with 'coconut LA' or 'porcelain LA'. Case summary : A 75-year-old woman was referred to our hospital because of chest discomfort and exertional dyspnoea. Doppler echocardiography revealed the presence of elevated filling pressure with significant LA dysfunction. A cardiac catheter examination revealed a quite impressive pulmonary capillary wedge pressure waveform with a steep up-slope and prominent v wave of 43 mmHg (mean: 15 mmHg). Multidetector row computed tomography revealed that LA was sandwiched by dense calcifications along the roof and bottom of the LA, and the posterior wall was compressed by a vertebral body. Integration of these functional and anatomical findings ultimately led to the diagnosis of 'stiff LA syndrome'. Discussion : She had a history of tuberculosis but no history of rheumatic fever or cardiac surgery. Thus, it appeared that the tuberculous pericarditis might have led to the calcified LA by long lasting inflammation. In this case, the LA was encased by a dense calcification and compressed by vertebral body from the posterior direction. Therefore, we speculated that the LA pressure could easily elevate even with a slight haemodynamic load in this special case, and thus eventually resulting in decompensated heart failure.